COVID‐19 Anosmia Reporting Tool: Initial Findings. (28th April 2020) - Kaye, Rachel; Chang, C. W. David; Kazahaya, Ken; Brereton, Jean; Denneny, James C.
Abstract : There is accumulating anecdotal evidence that anosmia and dysgeusia are associated with the COVID‐19 pandemic. To investigate their relationship to SARS‐CoV2 infection, the American Academy of Otolaryngology–Head and Neck Surgery developed the COVID‐19 Anosmia Reporting Tool for Clinicians for the basis of this pilot study. This tool allows health care providers to confidentially submit cases of anosmia and dysgeusia related to COVID‐19. We analyzed the first 237 entries, which revealed that anosmia was noted in 73% of patients prior to COVID‐19 diagnosis and was the initial symptom in 26.6%. Some improvement was noted in 27% of patients, with a mean time to improvement of 7.2 days in this group (85% of this group improved within 10 days). Our findings suggest that anomia can be a presenting symptom of COVID‐19, consistent with other emerging international reports. Anosmia may be critical in timely identification of individuals infected with SARS‐CoV2 who may be unwittingly transmitting the virus.